2022
DOI: 10.3390/ijerph20010029
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Clock Desynchronization and Insulin Resistance

Abstract: The circadian rhythm regulates biological processes that occur within 24 h in living organisms. It plays a fundamental role in maintaining biological functions and responds to several inputs, including food intake, light/dark cycle, sleep/wake cycle, and physical activity. The circadian timing system comprises a central clock located in the suprachiasmatic nucleus (SCN) and tissue-specific clocks in peripheral tissues. Several studies show that the desynchronization of central and peripheral clocks is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
3
0
1
Order By: Relevance
“…Chronic exposure to ALAN increases body mass and impairs glucose processing while maintaining equivalent caloric intake and locomotor activity patterns [ 169 ]. Insulin is another circulating hormone that is affected by ALAN and disrupted circadian rhythms, independent of food intake; although the precise mechanisms through which desynchronization of central and peripheral clocks contributes to insulin resistance has yet to be determined, a recent review of the literature [ 171 ] proposes two possible mediators of this interaction: the phosphatases belonging to the pleckstrin homology leucine-rich repeat protein phosphatase family and the deacetylase Sirtuin1 [ 172 ]. ALAN decreases glucose tolerance and insulin sensitivity in rodent models [ 168 , 173 ] and in human studies [ 174 ].…”
Section: Changing Environment and Consequences On Hormonal Rhythmsmentioning
confidence: 99%
“…Chronic exposure to ALAN increases body mass and impairs glucose processing while maintaining equivalent caloric intake and locomotor activity patterns [ 169 ]. Insulin is another circulating hormone that is affected by ALAN and disrupted circadian rhythms, independent of food intake; although the precise mechanisms through which desynchronization of central and peripheral clocks contributes to insulin resistance has yet to be determined, a recent review of the literature [ 171 ] proposes two possible mediators of this interaction: the phosphatases belonging to the pleckstrin homology leucine-rich repeat protein phosphatase family and the deacetylase Sirtuin1 [ 172 ]. ALAN decreases glucose tolerance and insulin sensitivity in rodent models [ 168 , 173 ] and in human studies [ 174 ].…”
Section: Changing Environment and Consequences On Hormonal Rhythmsmentioning
confidence: 99%
“…Фрагментація сну і переривчаста гіпоксія можуть підвищувати збудливість СНС, що супроводжується метаболічними порушеннями [67]. Занадто короткий сон знижує чутливість до інсуліну в адипоцитах і впливає на фосфорилювання серину/треонінкінази (Akt/протеїнкінази В), що здійснюється в інсуліновому сигнальному шляху [68]. Нарешті, занадто велика тривалість сну пов'язана з кількома факторами ризику захворюваності на МС, такими як депресія та низька фізична активність [63].…”
Section: птср і дисомніїunclassified
“…Central clock genes that regulate the biological function of circadian rhythm are period genes (PER1, PER2, and PER3), cryptochrome genes (CRY 1 and CRY2), BMAL1, CLOCK, and genes encoding nuclear receptor REV-ERB and ROR [20]. Misalignment between central and peripheral clocks seems to be the major underlying explanation for the association between circadian misalignment and impaired insulin signaling [21]. A recent study by Jouffe et al [22] suggested that disruption of BMAL1 activity significantly impacts the pathogenesis of metabolic and liver diseases.…”
Section: The Role Of the Circadian Clock In Insulin Resistance And Ma...mentioning
confidence: 99%